Against V2 as a general property of Old Romance languages - Martins, Ana Maria (2020)
This paper revisits the hypothesis that the verb-second property was a shared feature of the Old Romance languages by investigating Old Portuguese. It demonstrates, on the basis of positive empirical evidence, that Old Portuguese allowed clausal configurations that could not have been derived by a verb-second system. It is shown that clitic placement offers the means to pinpoint items that are categorically excluded from left-peripheral topic positions (non topic items – NTIs). Once NTIs are identified, the distinction between verb-third orders that can be accommodated within a verb-second system and those that cannot becomes clear-cut. It is shown that the test devised to recognize ‘true’ verb-third orders in Old Portuguese produces similar results when applied to other Old Iberorromance languages.